TSS-Seq analysis of low pH-induced gene expression in intercalated cells in the renal collecting duct - Izumi, Yuichiro (PLoS One, 2017)
Metabolic acidosis often results from chronic kidney disease; in turn, metabolic acidosis accelerates the progression of kidney injury. The mechanisms for how acidosis facilitates kidney injury are not fully understood. To investigate whether low pH directly affects the expression of genes controlling local homeostasis in renal tubules, we performed transcription start site sequencing (TSS-Seq) using IN-IC cells, a cell line derived from rat renal collecting duct intercalated cells, with acid loading for 24 h. Peak calling identified 651 up-regulated and 128 down-regulated TSSs at pH 7.0 compared with those at pH 7.4. Among them, 424 and 38 TSSs were ≥ 1.0 and ≤ -1.0 in Log(2) fold change, which were annotated to 193 up-regulated and 34 down-regulated genes, respectively. We used gene ontology analysis and manual curation to profile the up-regulated genes. The analysis revealed that many up-regulated genes are involved in renal fibrosis, implying potential molecular mechanisms induced by metabolic acidosis. To verify the activity of the ubiquitin-proteasome system (UPS), a candidate pathway activated by acidosis, we examined the expression of proteins from cells treated with a proteasome inhibitor, MG132. The expression of ubiquitinated proteins was greater at pH 7.0 than at pH 7.4, suggesting that low pH activates the UPS. The in vivo study demonstrated that acid loading increased the expression of ubiquitin proteins in the collecting duct cells in mouse kidneys. Motif analysis revealed Egr1, the mRNA expression of which was increased at low pH, as a candidate factor that possibly stimulates gene expression in response to low pH. In conclusion, metabolic acidosis can facilitate renal injury and fibrosis during kidney disease by locally activating various pathways in the renal tubules.